THE BENEFITS OF PEOPLE’S BUSINESS CREDIT TO UMKM VIEWED FROM THE PERSPECTIVE OF ECONOMIC LAW - Elvyani Permatasari; Amelia; Putri Dwi Rahayu; Firnando Sinaga; Maulana Rafli Noriska; Mustaqim (PT. Arsil Reka Engineering, 2024)
PERMENKO No. 1 year 2023 on Kredit Usaha Rakyat (KUR) is the foundation for the implementation of the program that supports the growth of the Micro, small, and Medium Enterprises(UMKM) sector. With the dominance of UMKM in the economic structure, the KUR program was initiated based on presidential instruction No. 6 of 2007, followed by an MoU between the government, guarantee institutions, and banks. KUR, run by certain banks, such as BRI, BNI, and Mandiri, gets unbankable UMKM. PERMENKO No. 1 year 2023 stipulates a maximum interest rate of 6%, a loan period of up to 7 years, and allows multiple loans subject to collectibility requirements. With a focus on UMKM that have difficulty accessing capital, the KUR program has succeeded in achieving effectiveness with the realization of reaching IDR 175,73 trillion as of September 2023. Although obstacles remain, such as the assumption of urbanicity and the unpreparedness of Micro business, KUR provides easier access to financing at low-interest rates, accelerating the economic growth of UMKM.